Seeking Flavivirus Cross-Protective Immunity - dos Santos Franco, Lorrany; Gushi, Letícia Tsieme; Luiz, Wilson Barros; Amorim, Jaime Henrique (Frontiers in Immunology, 2019)
The Flavivirus genus is composed by viral serocomplexes with relevant global epidemiological impact. Many areas of the world present both, vector fauna and geographical conditions compatible with co-circulation, importing, emergence and epidemics of flaviviruses of different serocomplexes. In this study, we aimed to identify both, immunological determinants and patterns of immune response possibly involved in flavivirus serocomplex cross-protection. We searched B and T cells epitopes which were thoroughly shown to be involved in flavivirus immunological control. Such epitopes were analyzed regarding their conservation, population coverage, and location along flavivirus polyprotein. We found that epitopes capable of eliciting flavivirus cross-protective immunity to a wide range of human populations are concentrated in proteins E, NS3 and NS5. Such identification of both, immunological determinants and patterns of immune response involved in flavivirus cross-protective immunity should be considered in future vaccine development. Moreover, cross-reactive epitopes presented in this work may be involved in dynamics of diseases caused by flaviviruses worldwide.